2009
DOI: 10.1016/j.biortech.2009.02.036
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen production by sorption-enhanced steam reforming of glycerol

Abstract: Catalytic steam reforming of glycerol for H 2 production has been evaluated experimentally in a continuous flow fixed-bed reactor. The experiments were carried out under atmospheric pressure within a temperature range of 400-700C. A commercial Ni-based catalyst and a dolomite sorbent were used for the steam reforming reactions and in-situ CO 2 removal. The product gases were measured by online gas analyzers. The results show that H 2 productivity is greatly increased with increasing temperature and the format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
89
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 171 publications
(100 citation statements)
references
References 28 publications
4
89
1
Order By: Relevance
“…Around 500 • C, the product gas distribution shows more of CH 4 and CO 2 conforming methanation and water gas shift reaction. At 600 • C increase in CO formation and decrease in CO 2 show that the reverse water gas shift reaction is predominant in (5) and (2) [31][32][33][34]. A nominal increment is observed in H 2 % at 600 • C temperature: Figure 9 and Table 3 explain the gas distribution at 600 • C 8 Figure 10(a) shows the glycerol conversion as a function of accelerated ageing for 20 experimental cycles (each cycle is 600 • C/1 h and 700 • C/1 h; feed rate is doubled) at 1 : 9 GWMRs.…”
Section: Effect Of Temperaturementioning
confidence: 98%
“…Around 500 • C, the product gas distribution shows more of CH 4 and CO 2 conforming methanation and water gas shift reaction. At 600 • C increase in CO formation and decrease in CO 2 show that the reverse water gas shift reaction is predominant in (5) and (2) [31][32][33][34]. A nominal increment is observed in H 2 % at 600 • C temperature: Figure 9 and Table 3 explain the gas distribution at 600 • C 8 Figure 10(a) shows the glycerol conversion as a function of accelerated ageing for 20 experimental cycles (each cycle is 600 • C/1 h and 700 • C/1 h; feed rate is doubled) at 1 : 9 GWMRs.…”
Section: Effect Of Temperaturementioning
confidence: 98%
“…Calcium-looping PCC, based on the reversible reaction CaO+CO 2 CaCO 3 , can be implemented using two parallel fluidized beds operated as a carbonator and a regenerative calciner, typically at ≥ 650 o C in ~ 15% CO 2 and ≥ 950 o C in ~100% CO 2 respectively 2 . Another area of application of CaO powder sorbents lies in steam reforming for the production of H 2 , whereby removal of the CO 2 co-product shifts the reaction equilibrium in favor of greater H 2 yields and purity 3 . Conditions for carbonation are comparable to those of PCC, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The present work concerns an alternative wet chemical powder synthesis method for CaZrO 3 /CaO sorbent powders, tested over 30 carbonation-decarbonation cycles. We show that the overall performance is superior to other Zr-modified CaO sorbents produced by solution-precipitation routes: near-stable multicycle CO 2 capture performance, after an initial rise, is demonstrated for mild conditions relevant to SESR involving carbonation at 650 °C in 15 % CO 2 and calcination in air at 800 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Lyon and Cole [3] have shown that H 2 rich syngas can be produced autothermally from methane and diesel fuel using a CLR system, also incorporating a calcium loop for CO 2 -sorption enhancement of the steam reforming. Previous work by the authors has demonstrated high reactant conversions using fuels with Ni and Ca looping such as methane [4], vegetable oil [5], crude glycerol [6], and waste cooking oil [7]. A crucial requirement of the CLR process is that the fuel can reduce the OTM during the beginning of the fuel feed step to enable the steam reforming to start from cycle to cycle.…”
Section: Introductionmentioning
confidence: 99%